2012
DOI: 10.1002/jcp.22853
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 negatively regulates intrinsic migration of highly aggressive breast cancer cells

Abstract: The small GTPase Cdc42 has been implicated as an important regulator of cell migration. However, whether Cdc42 plays similar role in all cancer cells irrespective of metastatic potential remains poorly defined. Here, we show by using three different breast cancer cell lines with different metastatic potential, the role of Cdc42 in cell migration/invasion and its relationship with a number of downstream signaling pathways controlling cell migration. Small interfering RNA (siRNA)-mediated knockdown of Cdc42 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 54 publications
5
27
0
1
Order By: Relevance
“…Furthermore, additional factors contributing to cell migration have also shown disparate effects in TNBC, with the Rho family GTPase Cdc42 found to negatively regulate cell migration in MDA-MB-231 cells while having a pro-migratory effect in Hs578T cells. 27 In recognizing the complexity of Smad3 action, impacted by both canonical and noncanonical phosphorylation, the specific phospho-Smad3 status may also have a role in the metastatic phenotypes of TNBC. As such, increased levels of Smad3 phosphorylated in the linker region (pSmad3L) have been detected in invasive human colorectal and hepatocellular cancers when compared to non-cancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, additional factors contributing to cell migration have also shown disparate effects in TNBC, with the Rho family GTPase Cdc42 found to negatively regulate cell migration in MDA-MB-231 cells while having a pro-migratory effect in Hs578T cells. 27 In recognizing the complexity of Smad3 action, impacted by both canonical and noncanonical phosphorylation, the specific phospho-Smad3 status may also have a role in the metastatic phenotypes of TNBC. As such, increased levels of Smad3 phosphorylated in the linker region (pSmad3L) have been detected in invasive human colorectal and hepatocellular cancers when compared to non-cancerous tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Although principally known to promote cell polarity, Cdc42 was recently reported to suppress migration of breast cancer cells (33). This finding contrasts with the promotility effects of activated Rac1 (34).…”
Section: Discussionmentioning
confidence: 95%
“…The additional spatial information provided insights about Cdc42 activation and underlined its clear inhibition. Furthermore, since Cdc42 has been associated with a migratory behaviour which seems to be dependent on the cell lines as recent studies have shown [40], this new technique could, given its fast acquisition rates, provide quantitative method to test the activation of Cdc42 and to associate it to a migratory or anti-migratory role depending on the cancer cell line.…”
Section: Resultsmentioning
confidence: 99%
“…We studied the activity of Cdc42, a member of the Rho GTPase subfamily, which regulates cellular functions such as cytoskeletal reorganization, cell division [34], signal transduction or vesicle trafficking [35]. Cdc42 plays a key role in cell motility as well as invasion and migration [36], [37], which are targeted processes involved in cancer disease [38][40]. Furthermore, Cdc42 over-activity has been associated to cancer [41][43], immune diseases [44] and neuronal disorders [45].…”
Section: Introductionmentioning
confidence: 99%